Taungya farming and poverty alleviation: the case of Onigambari forest reserve, Oyo State - Uzokwe, Veronica N.E.; Adejobi, A.O.; Olorundare, E. (African Journals Online, 2004)
Aforestation is a key forest policy in Nigeria and it usually goes with arable farming. This paper describes existing forest policies in Onigambari forest reserve, Oyo State and further examines the socioeconomic/demographic characteristics of farming households as they affect poverty status of the households in the study area. Two-stage random sampling technique was employed in sampling the respondents. Structured questionnaires were used to collect data on the socio-economic/demographic characteristics as well as agricultural output/input used by the farming households in 2002/2003 planting season. Logit model and scale rating methods were employed in analysing the data. The study revealed that the main features of existing forest policies are reservation, management, and protection of forest resources. A poverty tine of N1540 per month was obtained and 46% of the households were poor. Logit model showed that age, marital status and occupational level of household head, household size and farm income were significant at between 1% (p<0.01) and 5% (p<0.05) confidence limit The scale rating identified lack of financial resources, limited technical skill; information barriers and lack of infrastructure, in order of importance as constraints to agricultural production in the study area. It is, therefore, recommended that there is need to improve upon infrastructures in the study area to reduce farming household poverty.